1979
DOI: 10.1007/bf00427352
|View full text |Cite
|
Sign up to set email alerts
|

Urinary 4-hydroxy-3-methoxyphenylglycol is not a predictor for clinical response to amitriptyline in depressive illness

Abstract: The urinary excretion of 4-hydroxy-3-methoxyphenylglycol was compared in a group of 23 depressive patients and 27 control subjects of similar age. There was no difference between patients and controls although female controls excreted less than males. After 6 weeks' treatment with 150 mg daily of amitriptyline there was no correlation between therapeutic response and pretreatment urinary excretion value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
3

Year Published

1981
1981
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(13 citation statements)
references
References 18 publications
1
9
3
Order By: Relevance
“…As far as maprotiline is concerned, the results of the present study are not as conclusive as those of previous studies suggesting that urinary MHPG levels may predict response to treatment with this antidepressant (Scbatzberg et aL, 1981;Gaertner et al, 1982) but agree rather with those of Coppen et al (1979) concluding that urinary MHPG is not a predictor for clinical response to maprotiline in depressive illness. This discrepancy may be due to methodological factors.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…As far as maprotiline is concerned, the results of the present study are not as conclusive as those of previous studies suggesting that urinary MHPG levels may predict response to treatment with this antidepressant (Scbatzberg et aL, 1981;Gaertner et al, 1982) but agree rather with those of Coppen et al (1979) concluding that urinary MHPG is not a predictor for clinical response to maprotiline in depressive illness. This discrepancy may be due to methodological factors.…”
Section: Discussioncontrasting
confidence: 63%
“…Some authors Maas et aL, 1972;Scbildkraut, 1973;Beckmann and Goodwin, 1975;Hollister et al, 1978;Rosenbaum et aL, 1980;Carroll et aL, 1981;Schatzberg et al, 1981;Maas et aL, 1982;Maas et aL, 1984;Muscettola et aL, 1984) have reported that patients with low pretreatment urinary MHPG output respond more favourably to imipramine while patients with normal or high pretreatment levels of urinary MHPG show a better response to amitriptyline. However, these results have not been confirmed in other studies (Sachetti et al, 1976;Coppen et aL, 1979;Spiker et al, 1980). Moreover, in all these studies, the antidepressants used had a poor specificity for norepinephrine (NE) or serotonin (5-HT) reuptake.…”
Section: Introductioncontrasting
confidence: 58%
“…The most supportive data of an increased LC activity in depression is the decrease in LC activity observed with the administration of antidepressant drugs and electroconvulsive therapy (Grant and Weiss, 2001; West et al, 2009). There are few studies examining the number of LC neurons in depressed individuals because of the complication of antidepressant drugs (Chandley and Ordway, 2012); but there are several clinical studies that measured NE and its metabolites in the CSF of depressed subjects and the changes indicate an increase in LC activity (Coppen et al, 1979; Shaw et al, 1973; Wong et al, 2000; Ehnvall et al, 2003). At present, it is unknown if the 6-OHDA-treated animals with increased LC activity had altered synaptic NE levels compared to vehicle-treated animals.…”
Section: Discussionmentioning
confidence: 99%
“…Although the original catecholamine hypothesis of major depression stated that a deficient NE delivery to its receptors in the CNS was one of the main causes of depression, 77 studies of NE or its metabolites in CSF, plasma, or urine, or of components of the noradrenergic system in post-mortem brain samples, reported indices suggestive of decreased, [79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96] normal, [97][98][99][100][101][102][103][104][105] or increased [106][107][108][109][110] delivery of NE to its intended receptors in the CNS or periphery. It should be noted that almost all of the prior studies of CSF NE or its metabolites in depressed patients were based on single time points.…”
Section: The Locus Ceruleus Norepinephrine Systemmentioning
confidence: 99%